2003
DOI: 10.1172/jci18509
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo analysis of human memory CD4 T cells specific for hepatitis C virus using MHC class II tetramers

Abstract: Containment of hepatitis C virus (HCV) and other chronic human viral infections is associated with persistence of virus-specific CD4 T cells, but ex vivo characterization of circulating CD4 T cells has not been achieved. To further define the phenotype and function of these cells, we developed a novel approach for the generation of tetrameric forms of MHC class II/peptide complexes that is based on the cellular peptide-exchange mechanism. HLA-DR molecules were expressed as precursors with a covalently linked C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
165
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 43 publications
7
165
0
Order By: Relevance
“…Importantly, whereas after spontaneous or treatment induced viral clearance tetramer+ CD4+ T cells levelled off at frequencies between 0.01% and 0.1%, the frequency further declined to very low (<0.01%) or undetectable levels in patients who developed chronic infection. This finding is consistent with a previous study employing an HCV specific HLA-DR4 tetramer that found a significant tetramer+ CD4+ T cell population in long-term recovered patients but not in patients with chronic hepatitis C [8]. Similarly, with the HLA-DR1 tetramer we found maintained levels of tetramer+ CD4+ T cells in three spontaneously recovered patients, one of whom had cleared HCV more than 20 years before, but only low frequencies in patients with chronic hepatitis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, whereas after spontaneous or treatment induced viral clearance tetramer+ CD4+ T cells levelled off at frequencies between 0.01% and 0.1%, the frequency further declined to very low (<0.01%) or undetectable levels in patients who developed chronic infection. This finding is consistent with a previous study employing an HCV specific HLA-DR4 tetramer that found a significant tetramer+ CD4+ T cell population in long-term recovered patients but not in patients with chronic hepatitis C [8]. Similarly, with the HLA-DR1 tetramer we found maintained levels of tetramer+ CD4+ T cells in three spontaneously recovered patients, one of whom had cleared HCV more than 20 years before, but only low frequencies in patients with chronic hepatitis.…”
Section: Discussionsupporting
confidence: 93%
“…This is the first HCV specific HLA class II tetramer to be tested and validated using epitope specific CD4+ T cell clones and we could demonstrate that this tetramer possesses similar sensitivity and specificity to HIV or influenza specific HLA class II tetramers characterized in a similar manner [8][11]. In addition, we took advantage of the fact that the HCV peptide used for the tetramer synthesis was highly targeted in our HLA-DR1+ study cohort.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CTL responses to HLA-A2 and non-HLA-A2 epitopes showed similar kinetics, frequencies, and phenotypes. Thus, future studies might reasonably track defined epitopes, rather than requiring individual mapping, as is the case in, for example, HCV [1719]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, HLA class II tetramers were used to visualize HCV-specific CD4+ T cells in the blood of all HCV-infected subjects regardless of infection outcome (Lucas et al , 2007). CD4+ T cell populations remain detectable in the circulation of subjects who resolved the infection but frequencies dropped below the level of detection in those who followed a persistent course (Day et al , 2003; Lucas et al , 2007). This is consistent with comprehensive mapping of CD4+ T cell responses in individuals with chronic versus resolved infections (Day et al , 2002; Schulze zur Wiesch et al , 2005).…”
Section: Cellular Immunity To Hcvmentioning
confidence: 92%